B.C. student’s VR tech gets lift off in experiment on astronaut loneliness | Globalnews.ca - Karamali, Kamil (Global News, 2021)
SFU PhD student Katerina Stepanova created a VR experience that takes viewers through several settings to help them feel more grounded while on a long-duration space flight.
Keywords: mediaCoverage; proj--SIRIUS-earthgazing-newscoverage